COMPENSATION AND SOCIAL WORKING ENVIRONMENT INFLUENCING UNMET NEEDS OF FAMILY PLANNING - Deby Indah Permatasari; Anneke Meyvia Silvi (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2019)
Background: The incidence of unmet needs of family planning is one of the performance indicators of Family Planning Outreach Workers. There were 30 sub-districts in Surabaya, but only two sub-districts reached the number of unmet need incidences at 7.3% as required by the government standard in 2016.Aims: The study aimed to analyze the correlation and effect of performance factors, especially salary system and social working environment towards the number of unmet need incidences in Surabaya.Method: This study employed descriptive quantitative research with a cross-sectional design. The data were obtained from questionnaires, filled out by 30 teams of Family Planning Outreach in Surabaya as respondents selected by using a total sampling method. The data were analyzed with descriptive statistical tests of cross-tabulation between salary system, workplace, and incidence of unmet need.Results: A better condition of salary system did not determine the standard number of unmet need incidences. Two districts that perceives fair social working environment have the number of unmet need incidences that follows the standard of ≤7.3%. Whereas only 10 districts have perceived a good social working system which result in the unachieved standard number of unmet need incidences at >7.3%.Conclusion: There is no significant correlation or influence between salary or compensation system with the number of unmet need incidences. However, there are not significant correlation and influence between the social working environment and the number of unmet need incidences. Therefore, improvements in the social working environment should be made to achieve the goal of family planning program.Keywords: family planning outreach workers, salary system, social working environment, unmet need.